2003
DOI: 10.1046/j.1469-0691.2003.00764.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diagnosis of a vascular prosthesis infection, due to Propionibacterium acnes, by amplification and sequencing of 16S rDNA

Abstract: We describe a case of indolent vascular prosthesis infection due to Propionibacterium acnes. The microorganism was identified only by amplification and sequencing of 16S rDNA, while standard cultures remained negative. This observation underscores the usefulness of molecular techniques for the diagnosis of infection caused by fastidious microorganisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…However, different studies have reported the involvement of Propionibacteria spp. in serious infections, such as endocarditis, postoperative endophthalmic infections (Hykin et al , 1994; Jakab et al , 1996; Le Page et al , 2003), osteomyelitis, arthritis and sarcoidosis (Ishige et al , 1999). A recent case study (Schneider et al , 2000) documented the clinical sequelae of three incidents of platelet contamination by Propionibacterium acnes .…”
mentioning
confidence: 99%
“…However, different studies have reported the involvement of Propionibacteria spp. in serious infections, such as endocarditis, postoperative endophthalmic infections (Hykin et al , 1994; Jakab et al , 1996; Le Page et al , 2003), osteomyelitis, arthritis and sarcoidosis (Ishige et al , 1999). A recent case study (Schneider et al , 2000) documented the clinical sequelae of three incidents of platelet contamination by Propionibacterium acnes .…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13] Eight of these cases had previous cardiac operation history and prosthesis implantation. The duration between surgery and presentation of infective endocarditis varied from 3 weeks to 4 years.…”
mentioning
confidence: 99%
“…PCR amplification and sequencing of the 16S rRNA gene have been used successfully in previous studies to detect the slow-growing P. acnes in vascular prosthesis infections and infective heart valve endocarditis [16, 17]. In these cases, no bacteria were observed in the Gram stain, and no growth was observed after culturing.…”
Section: Discussionmentioning
confidence: 99%
“…They reported improvement in the percentage of identification (up to the species level) and in the detection time. This combined method might be superior to culture methods in the diagnosis of bacterial infections if the patient is receiving empirical antibiotics, if the infection is caused by bacteria with unusual growth requirements, or if the pathogen is of an unexpected strain [16]. …”
Section: Discussionmentioning
confidence: 99%